25-hydroxyvitamin D status of pregnant women is associated with the use of antenatal vitamin supplements and ambient ultraviolet radiation. (21st April 2016) - Jones, A. P.; Rueter, K.; Siafarikas, A.; Lim, E.-M.; Prescott, S. L.; Palmer, D. J.
Abstract : Previous research suggests prevalent vitamin D deficiency in pregnant women residing in South Australia and the Eastern Seaboard, however recent data from Perth, Western Australia (WA) is lacking. This cross-sectional study of n =209 pregnant women (36–40 weeks of gestation, 84% white Caucasian) reports on the vitamin D (25[OH]D) status of a contemporary population of pregnant women in Perth, WA, with a focus on the relative contributions of supplemental vitamin D and ambient ultraviolet (UV) radiation to 25(OH)D levels. Mean (SD ) season-adjusted 25(OH)D levels were 77.7 (24.6) nmol/l. The prevalence of vitamin D deficiency (25[OH]D<50 nmol/l) was 13.9%. Ambient UV radiation levels in the 90 days preceding blood draw were significantly correlated with serum 25(OH)D levels (unstandardized coefficient 2.82; 95% CI 1.77, 3.86, P <0.001). Vitamin D supplementation expressed as dose per kg of body weight was also positively correlated with serum 25(OH)D levels (unstandardized coefficient 0.744; 95% CI 0.395, 1.092, P <0.001). In conclusion, this study finds that vitamin D deficiency in a predominantly white Caucasian cohort of pregnant women is less prevalent than has been reported in other studies, providing useful information relating to supplementation and screening in this, and similar, populations.